2013
DOI: 10.1111/1475-6773.12048
|View full text |Cite
|
Sign up to set email alerts
|

Do Clinical Standards for Diabetes Care Address Excess Risk for Hypoglycemia in Vulnerable Patients? A Systematic Review

Abstract: Objective To determine if diabetes clinical standards consider increased hypoglycemia risk in vulnerable patients. Data Sources MEDLINE, the National Guidelines Clearinghouse, the National Quality Measures Clearinghouse, and supplemental sources. Study Design Systematic review of clinical standards (guidelines, quality metrics, or pay-for-performance programs) for glycemic control in adult diabetes patients. The primary outcome was discussion of increased risk for hypoglycemia in vulnerable populations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…34 The higher rates of ED visits and hospitalizations for IHEs among older insulin-treated patients with diabetes suggest that individualizing glycemic targets by balancing hypoglycemia risks with long-term benefits of glycemic control is appropriate. 22, 35–37 Updated guidelines and treatment recommendations are now advising glycemic targets be relaxed for patients with advanced age, high risk of hypoglycemia or shorter life expectancy.…”
Section: Discussionmentioning
confidence: 99%
“…34 The higher rates of ED visits and hospitalizations for IHEs among older insulin-treated patients with diabetes suggest that individualizing glycemic targets by balancing hypoglycemia risks with long-term benefits of glycemic control is appropriate. 22, 35–37 Updated guidelines and treatment recommendations are now advising glycemic targets be relaxed for patients with advanced age, high risk of hypoglycemia or shorter life expectancy.…”
Section: Discussionmentioning
confidence: 99%
“…Further, wellpublicized results in 2008-2009 from three trials (ACCORD [19], ADVANCE [20], and VADT [21]) suggested that elderly adults may not gain macrovascular benefits from aggressive glycemic control; rather, intensive therapy was associated with increased risk of severe hypoglycemia and may increase mortality. With a few exceptions (42,43), most diabetes guidelines did not emphasize, until very recently, adjustment of glycemic targets through evaluating an individual's hypoglycemia risk factors (2,3,44).…”
Section: Discussionmentioning
confidence: 99%
“…Few guidelines provide recommendations on how to de-intensify or address hypoglycemia risk. [22] The most relevant recommendations are from the AGS, which cautions against polypharmacy, [12] and Choosing Wisely/AGS, which recommends against using medications other than metformin to achieve HbA 1C  < 7.5% in most older patients. [23] …”
Section: Introductionmentioning
confidence: 99%